2019
DOI: 10.1017/s0014479719000292
|View full text |Cite
|
Sign up to set email alerts
|

Competition dynamics of Parthenium hysterophorus in direct-seeded aerobic rice fields

Abstract: Parthenium hysterophorus is a prolific invasive weed species, which infests many crops in over 40 countries around the world. A 2-year field study was carried out to quantify the potential impacts of this weed on direct-seeded rice. Parthenium weed was allowed to compete for 2, 4, 6 or 8 weeks after crop emergence, while full season weedy and weed-free plots were maintained as controls. Parthenium weed plants grew taller and attained more biomass as the competition duration prolonged. The yield and yield-relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Parthenium is rapidly spreading in various parts of Punjab, KP and Kashmir, and is becoming a dominant weed in different terrestrial ecosystems. The weed is highly invasive and is reported as a major weed for agro-ecosystems in Pakistan [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Parthenium is rapidly spreading in various parts of Punjab, KP and Kashmir, and is becoming a dominant weed in different terrestrial ecosystems. The weed is highly invasive and is reported as a major weed for agro-ecosystems in Pakistan [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its robust growth patterns, efficient reproductive biology, rapid resource acquisition, ability to tolerate abiotic stress, allelopathic capacity, and phenotypic plasticity are among the pivotal traits contributing to its invasiveness and competitiveness [4,[10][11][12][13][14]. Notably, parthenium weed infestations have been linked to significant yield losses in major field crops such as sorghum, maize (Zea mays L.), and rice (Oryza sativa L.) [15][16][17][18]. A recent study by Bajwa et al [19] reported a grain yield reduction of up to 81% in sorghum due to competition from parthenium weed in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…The small sized seed (2 mm in length) are easily dispersed by water and wind, but most of the spread across the regions were mainly through farm vehicles and machinery and as contaminants in the exported animals' feed as well as other crop seed lots (Kaur et al, 2014). The rapid spread of P. hysterophorus can be attributed to its seed production's prolific nature and its high capacity to adapt to a wide range of environmental conditions (Annapurna & Singh, 2003;Bajwa et al, 2020). Nevertheless, some variation may persist from the plant-environment interactions, ultimately influencing weed invasiveness or infestations (Vilà et al, 2021).…”
Section: Introductionmentioning
confidence: 99%